Manajemen Konflik dalam Komunikasi Antarpribadi:: Sintesis Perspektif Islam dan Teori Komunikasi Kontemporer - Fachrur Rizha; Kartini; Ali Mustafa (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2026)
Interpersonal communication is an essential aspect of human life and is inherently accompanied by the potential for conflict arising from differences in interests, perceptions, and perspectives. Conflict is not always detrimental; when managed constructively, it can serve as a means of strengthening interpersonal relationships. Although numerous studies have examined conflict management and its resolution from an Islamic perspective, research integrating interpersonal communication with Islamic values remains limited. This study aims to examine the concept of conflict management in interpersonal communication from an Islamic perspective, highlighting the positive outcomes of conflict and the strategies for its resolution. The study employed a library research method by reviewing relevant books, scholarly journals, and other academic literature. The findings reveal that Islam emphasizes conflict resolution through the principles of islah (reconciliation), musyawarah (consultation), tabayyun (verification), justice, patience, and forgiveness. Properly managed conflict can enhance communication quality, strengthen interpersonal relationships, foster trust, and promote personal development. The novelty of this study lies in integrating Islamic conflict resolution principles with interpersonal communication, thereby positioning conflict not merely as a problem to be resolved but as an opportunity to build more harmonious, productive, and sustainable relationships through open communication, empathy, and respect for differences.